Identifikasi Pengembangan Kota Jayapura Sebagai Kawasan Minapolitan - Jansen Stevenson Lau; Asep Agus (Program Studi Perencanaan Wilayah dan Kota Universitas Pasundan, 2016)
The coastal area is ecologically is the junction between the terrestrial and marine ecosystems. Landward covering the ground, either dry or submerged in seawater, and is still influenced by the physical properties of the ocean such as tidal, wave and wave and saline water intrusion development of the region minapolitan this will greatly affect the development of the region both in terms of economy and also the independence of the region. Development of the city of Jayapura as minapolitan region due Jayapura city has such great potential of fisheries in the form of fisheries and aquaculture along the coral diversity. Regional development minapolitan be relevant to coastal areas because, in general fisheries and marine sector is the main livelihood of most coastal communities, both individuals, households, and small and medium enterprises, and cooperatives. see the above it writer felt the need to do a study with the title of city development tutorial Jayapura as minapolitan region.